Dural identity process for virtual community participation and impact of gender composition. Issue 2 (3rd April 2017) - Shen, Kathy Ning; Zhao, Fang; Khalifa, Mohamed
Abstract : Purpose: Unlike the earlier research that examines gender impact at the individual level, the purpose of this paper is to examine whether and how gender composition of virtual communities (VCs) interact with identity-related needs, namely identification and identity confirmation in affecting VC participation. Design/methodology/approach: Drawing on the theories and previous research of social identity and organizational identification, the study developed and tested a new research model through an online survey involving three male dominant VCs and one female-dominant VC. Findings: The results show that identification and identity confirmation are two independent antecedents for VC participation. Identification is a significant and stable determinant for members' VC participation regardless of gender composition, but the effect of identity confirmation on VC participation is only significant for those in a female-dominant VC. Research limitations/implications: The results of the study represent the first attempt to empirically examine the dual identity processes for VC participation. The results also imply that gender composition shapes, to some extent, VC members' communication strategies, contents, and social interaction norms. Gender composition also affects the expectations for VC participation in terms of identification and identity confirmation. Practical implications: The results of the study offer practical value for VC design and management, marketing through social media, as well as online education such as virtual team learning and teaching. Originality/value: This study extends and advances the existing research in several ways. To the best of the authors knowledge, the study is the first of its kind to address the interplays among identification, identity confirmation, and VC participation from a gender composition perspective.